Changes in immune response during pig gestation with a focus on cytokines - Velez, Carolina (2024)
Pigs have the highest percentage of embryonic death not associated with specific diseases of all livestock species, at 20–45%. During gestation processes, a series of complex alterations can arise, including embryonic migration and elongation, maternal immunological recognition of pregnancy, and embryonic competition for implantation sites and subsequent nutrition requirements and development. Immune cells and cytokines act as mediators between other molecules in highly complex interactions between various cell types. However, other non-immune cells, such as trophoblast cells, are important in immune pregnancy regulation. Numerous studies have shed light on the crucial roles of several cytokines that regulate the inflammatory processes that characterize the interface between the fetus and the mother throughout normal porcine gestation, but most of these reports are limited to the implantational and peri-implantational periods. Increase in some proinflammatory cytokines have been found in other gestational periods, such as placental remodeling. Porcine immune changes during delivery have not been studied as deeply as in other species. This review details some of the immune system cells actively involved in the fetomaternal interface during porcine gestation, as well as the principal cells, cytokines, and molecules, such as antibodies, that play crucial roles in sow pregnancy, both in early and mid-to-late gestation.